Comparison of System Methods (Table Form) With Semi Systems from Cost Aspects in the Apartment Meikarta Project - Anjas Handayani; Komarul Umam (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2020)
Meikarta Apartment Project at the beginning of the implementation of the method that is used is a formwork system so that the spring mounting groove formwork and casting becomes inhibited. With some consideration, the formwork method was changed from the Semi si stem method to the System (Table Form). Therefore an analysis of costs and time in formwork planning is carried out in order to obtain effective and efficient planning results. At this stage begins with field observations, literature studies include information gathering, problem formulation activities, primary and secondary data and data analysis processing with the Analysis of SNI Work Unit Price (AHS-SNI) 2018 To produce the price of formwork work which includes wages, materials and tool. Based on the results of the analysis carried out on each formwork method, it was concluded that the Cost of Formwork System Work (Table Form) is cheaper compared to Semi system. The total cost of work using the Semi system as much as Rp. 4,837,286,252.27 While using formwork System (Table Form) as much as Rp. 3,724,594,795.77. This shows that work using the System (Table Form) is cheaper by Rp. 1,112,691,456.50 or around 23%.